Role of P2X7 Receptors in Immune Responses During Neurodegeneration - Oliveira-Giacomelli, Ágatha; Petiz, Lyvia Lintzmaier; Andrejew, Roberta; Turrini, Natalia; Silva, Jean Bezerra; Sack, Ulrich; Ulrich, Henning (Frontiers in Cellular Neuroscience, 2021)
P2X7 receptors are ion-gated channels activated by ATP. Under pathological conditions, the extensive release of ATP induces sustained P2X7 receptor activation, culminating in induction of proinflammatory pathways with inflammasome assembly and cytokine release. These inflammatory conditions, whether occurring peripherally or in the central nervous system (CNS), increase blood-brain-barrier (BBB) permeability. Besides the well-known involvement in neurodegeneration and neuroinflammation, the P2X7 receptor may induce BBB disruption and chemotaxis of peripheral immune cells to the CNS, resulting in brain parenchyma infiltration. For instance, despite common effects on cytokine release, P2X7 receptor signalling is also associated with metalloproteinase secretion and activation, migration and differentiation of T lymphocytes, monocytes and dendritic cells. Here we highlight that peripheral immune cells mediate the pathogenesis of Multiple Sclerosis and Parkinson’s and Alzheimer’s disease, mainly through T lymphocyte, neutrophil and monocyte infiltration. We propose that P2X7 receptor activation contributes to neurodegenerative disease progression beyond its known effects on the central nervous system. This review discusses how P2X7 receptor activation mediates responses of peripheral immune cells within the inflamed CNS, as occurring in the aforementioned diseases.